Mendelian randomization analysis of gut microbiota-immune cell interactions in malignant neoplasm of nasopharynx - Qicong Chen; Gang Wang; Jingcheng Shu; Xiaosu Zou; Weiwei Miao; Wenqian Nong; Min Li; Guiping Lan; Wenlin Huang; Xueying Huang; Honglin Luo; Shenhong Qu (AMB Express)
Abstract Observational studies have suggested associations among the gut microbiome, immune cells, and the risk of malignant neoplasms of nasopharynx. However, the causality of these relationships remains unclear. Thus, we conducted multiple Mendelian Randomization analyses to estimate the causal association of gut microbiota with the risk of malignant neoplasms of nasopharynx and to evaluate the mediating effect of immune cells on this causal pathway. Genetic variants extracted from genome-wide association studies of human gut microbiota compositions (n = 211), immune cell traits (n = 731) and malignant neoplasms of nasopharynx served as instrumental variables for calculating causal associations and mediating effects. Four gut microbiota compositions and eight immune cell traits exhibited detrimental causal effects, while three gut microbiota compositions and fifteen immune cell traits demonstrated protective effects. Interestingly, the causal association of genus Candidatus Soleaferrea id.11350 was no longer significant after adjusting for two established immune cell traits (HLA DR +  + monocyte %leukocyte and HLA DR +  + monocyte % monocyte). Moreover, HLA DR +  + monocyte %leukocyte exhibited a mediating effect (OR 0.75, 95% CI 0.59–0.96) on the causal pathway of genus Candidatus Soleaferrea id.11350–malignant neoplasms of nasopharynx, with a mediating proportion of 21.59%. To our knowledge, this study is the first to identify potential therapeutic targets and elucidate mechanistic insights for malignant neoplasms of nasopharynx interventions involving gut microbiota and immune cell traits; however, these findings warrant further validation through adequately powered randomized clinical trials (RCTs). Graphical abstract